2023
DOI: 10.3390/jcs7100417
|View full text |Cite
|
Sign up to set email alerts
|

Aryloxyphosphazene-Modified and Graphite-Filled Epoxy Compositions with Reduced Flammability and Electrically Conductive Properties

Anastasia Konstantinova,
Pavel Yudaev,
Alexey Orlov
et al.

Abstract: A method has been developed for producing an epoxy composition based on a low-viscosity epoxy-resorcinol resin, a phosphazene-containing curing agent, isophoronediamine, and thermally expanded graphite as a filler. The degree of cure and the absence of side reactions during the curing process were confirmed using IR spectroscopy. The influence of the content of phosphazene-containing curing agent and filler on the physico-mechanical properties of the composition, its fire resistance, and antistatic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Organophosphorus flame retardants (OPFRs) are common polymer additives employed for flame retardation and plasticization [1][2][3]. In recent years, OPFRs and related degradation products and analogues have been commonly found in water [4], dust [5], sludge [6], and various foods [7][8][9][10][11], and are distributed worldwide [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus flame retardants (OPFRs) are common polymer additives employed for flame retardation and plasticization [1][2][3]. In recent years, OPFRs and related degradation products and analogues have been commonly found in water [4], dust [5], sludge [6], and various foods [7][8][9][10][11], and are distributed worldwide [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Cahit Orek et al [14] solved the problem of gold(I) N-heterocyclic monocarbene-adsorbing graphene as a drug nanocarrier via calculations. Studies have shown that graphene and its derivatives can effectively improve the mechanical properties of polymers, Anastasia Konstantinova et al [15] ascertained that the incorporation of a phosphazene-containing curing agent, coupled with thermally expanded graphite, markedly enhanced the fire resistance, as well as the physical and mechanical characteristics, of epoxy resin. However, it could only happen if graphene nanoplatelets were well dispersed in the polymer matrix [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are used to produce composites with other polymers, due to their diversified properties such as ease of processability, enhanced physical and mechanical properties, good adhesion with other materials, resistance towards chemicals, and electrical insulation. Despite these admirable properties, they also possess high flammability and low fire resistance, which hinders the advantage of the final product [8][9][10]. Epoxy resins are well known for their versatility and compatibility with various polymers, making them ideal candidates for blending with PBzs.…”
Section: Introductionmentioning
confidence: 99%